Evolution of videolaryngoscopy in pediatric population - Anju Gupta; Ridhima Sharma; Nishkarsh Gupta (Wolters Kluwer Medknow Publications, 2021)
Direct laryngoscopy has remained the sole method for securing airway ever since the inception of endotracheal intubation. The recent introduction of video-laryngoscopes has brought a paradigm shift in the pratice of airway management. It is claimed that they improve the glottic view and first pass success rates in adult population. The airway management in children is more challenging than adults. The role of videolaryngoscopy for routine intubation in children is not clearly proven. This review attempts to discuss various videolaryngosocpes available for use in pediatric patients.